A review of theoretical salt weathering studies for stone heritage - Oguchi, Chiaki T.; Yu, Swe (Progress in Earth and Planetary Science, 2021)
Salt weathering can cause substantial deterioration of natural rocks, building stones, masonry materials, monuments, and engineering structures. Nearly two centuries of salt weathering studies, both theoretically and empirically, have manifested its power as well as its complexity. This paper attempts to unite the kinds of literature assess the various theories in the light of the combined information. The theoretical approaches concerning the most cited mechanisms of salt weathering such as crystallization, hydration and thermal expansion of crystalline salts are thoroughly reviewed. It is understood that there is no universally acceptable hard and sound theoretical information on this topic yet. More precise theories should be developed to elucidate the complications of the mechanisms of salt weathering as well as to interpret the results of empirical studies.